Poly(aryleneethynylene)s (PAE) as paradigmatic sensor cores - Bunz, Uwe H. F.; Seehafer, Kai; Bender, Markus; Porz, Michael (Chemical Society reviews, 2015)
We describe poly(aryleneethynylene)s (PAE) as powerful sensor cores. We discuss concepts (super quenching, molecular wire effect, multivalency) that were developed using PAEs and also the relationship that connects side chain structure (polar, polyelectrolyte, etc., number of ionic groups per repeat, position) and optical properties such as quantum yields. In the second part of the review we discuss applications of PAEs in their interaction with sensor targets; metal cations, fluoride and other anions, explosives, proteins and whole cells being the target for PAEs, while cationic PAEs have been used for the transfection of eukaryotic cells with RNA.
Gesehen am 21.10.2020